Successful treatment with ustekinumab of psoriasis vulgaris in a patient undergoing hemodialysis. Issue 1 (24th June 2015) - Nimmannitya, Kulsupa; Tateishi, Chiharu; Mizukami, Yukari; Hamamoto, Kae; Yamada, Shinsuke; Goto, Hitoshi; Okada, Shigeki; Tsuruta, Daisuke
Abstract: Psoriasis is a common chronic inflammatory skin disease but psoriasis patients with renal impairment undergoing dialysis are not frequently seen. Furthermore, the published work contains little information on the treatment with biologic drugs of patients with end‐stage renal disease. We describe a 57‐year‐old man with refractory plaque‐type psoriasis and end‐stage renal disease due to polycystic kidney disease undergoing hemodialysis. He had tried topical medications and ultraviolet therapy for many years and was then treated with ustekinumab (an interleukin‐12 and interleukin‐23 blocker), which resulted in good clinical response along with stable renal function. After a few years of therapy, no side‐effects have been observed. Our experience with this patient expands the spectrum of ustekinumab to include psoriasis patients with renal failure undergoing hemodialysis.